2001
DOI: 10.1021/jp010038d
|View full text |Cite
|
Sign up to set email alerts
|

Stable Ti/IrOx−Sb2O5−SnO2 Anode for O2 Evolution with Low Ir Content

Abstract: Titanium anodes coated with a ternary iridium, antimony, and tin oxide mixture (Ti/IrO x −Sb2O5−SnO2) were investigated for oxygen evolution. In the active oxide coating, SnO2 serves as a dispersing agent, Sb2O5 as a dopant, and IrO x as a catalyst. Experimental results showed that the Ti/IrO x −Sb2O5−SnO2 electrode containing only 10 mol % of IrO x nominally in the coating had a service life of 1600 h in 3 M H2SO4 solution under a current density of 1 A cm-2 at 35 °C, compared with 355 h for Ti/IrO x under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(111 citation statements)
references
References 37 publications
5
105
0
1
Order By: Relevance
“…These include RuO 2 , IrO 2 , PbO 2 and SnO 2 that are widely used in areas such as chlorine production, water electrolysis, ozone production, and electro-oxidation of organics in wastewater treatment. [1][2][3][4][5] For wastewater treatment, an electrode material having high efficiency and selectivity toward oxidation of organic compounds is desired.One candidate electrode material is the antimony doped tin oxide on Ti. This electrode is generally written as Ti/SnO 2 -Sb 2 O 5 .…”
mentioning
confidence: 99%
“…These include RuO 2 , IrO 2 , PbO 2 and SnO 2 that are widely used in areas such as chlorine production, water electrolysis, ozone production, and electro-oxidation of organics in wastewater treatment. [1][2][3][4][5] For wastewater treatment, an electrode material having high efficiency and selectivity toward oxidation of organic compounds is desired.One candidate electrode material is the antimony doped tin oxide on Ti. This electrode is generally written as Ti/SnO 2 -Sb 2 O 5 .…”
mentioning
confidence: 99%
“…[16][17][18] Firstly the titanium plate was pre-treated before coating. Three coating materials (CM) SnCl 4 , SbCl 3 and IrCl 3 .xH 2 O were dissolved in acetic acid (AA) and ethylene-glycol (EG) in ratios of (CM:AA:EG) (2 ml:2 ml:10 ml), (2 g:2 ml:10 ml) and (0.1 g:2 ml:10 ml) respectively at 60°C for 1 hr.…”
Section: Anode Coatingmentioning
confidence: 99%
“…15 In recent studies it was reported that the addition of iridium oxide (IrO 2 ) to the SnO 2 -Sb 2 O 5 coating greatly increases service life. 16,17 This has been attributed to the incorporation of IrO 2 in the SnO 2 -Sb 2 O 5 coating by diffusion during electrode preparation. In Ti/SnO 2 -Sb 2 O 5 -IrO 2 anode, SnO 2 acts as a dispersing agent, Sb 2 O 5 as a doping agent and IrO 2 acts as a catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, the anodes were calcined at 500°C for 1 h. More details of the preparation procedures can be found elsewhere. 9,12,13 The average thickness of the film was about 3 µm.…”
Section: Electrochemistrymentioning
confidence: 99%
“…9 However, IrO 2 is much more expensive and slightly lower in activity than RuO 2 . To save cost and/or to improve the coating property, other components are usually mixed.…”
Section: Introductionmentioning
confidence: 99%